Polyurethane microbubble elastomer for shoe material and preparation method thereof
By using a foaming agent that is well compatible with the polymer main material, adjusting the composition and proportion of the foaming agent, the problem of uneven distribution of bubble cells in existing polyurethane foamed shoes is solved, and the high polyurethane microfoam elastomer is achieved Density, strength and comfort.
Patent Information
- Application Number
- CN202310986235.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-07
- Publication Date
- 2025-02-14
AI Technical Summary
The existing polyurethane foamed shoe materials use incompatible foaming agents, resulting in uneven distribution of bubble cells and inconsistent sizes, which affects the strength, resilience and service life of shoe products.
The type of foaming agent is well compatible with the common polymer main materials. By adjusting the composition and proportion of the foaming agent, the uniform distribution and dimensional consistency of the bubble cells are ensured, thereby improving the strength and comfort of the shoe material.
The delicate cell structure of polyurethane microbubble elastomer is realized, the density, compression strength and rebound rate of the material are improved, and the comfort requirements of sole materials are met.
Smart Images

Figure CN119431719A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a polyurethane micro-bubble elastomer for shoe materials and a preparation method thereof, and belongs to the field of polyurethane elastomers. Background Art
[0002] Polyurethane shoe materials are the basic raw materials for high-quality shoe products, with the advantages of low density, good rebound performance and outstanding comfort.
[0003] CN1189499C discloses a method for preparing a polyether-based polyurethane microporous elastomer, comprising: 1. preparing a polyol mixture-component A, mixing a high-activity low-unsaturation polyether polyol, a polymer polyol, a chain extender, water, a catalyst, and a surfactant in a weight ratio of: high-activity low-unsaturation polyether polyol: polymer polyol: chain extender: water: catalyst: surfactant = 100: 5-15: 5-15: 0.3-1.2: 1.0-2.0: 0.3-1.0; after fully mixing, cooling, discharging, and sealing. 2. Preparation of modified isocyanate-terminated semi-prepolymer-B component: diisocyanate, low unsaturation polyether polyol and low molecular weight modifier that can react with isocyanate are reacted in a weight ratio of diisocyanate: low unsaturation polyether polyol: low molecular weight modifier = 80-90: 5-10: 5-10, and the product is sealed and stored; 3. Keep the temperature of component A at 30-35°C and the temperature of component B at 40-45°C, mix components A and B fully, quickly inject into the mold for molding, and after ripening, demould to obtain the product. Polyether-based polyurethane microporous elastomer is used for shock-proof and cushioning materials, such as automotive soft parts and shoemaking.
[0004] CN101328254B discloses a polyester polyurethane microporous elastomer added with low-cost polycarbonate polyol for making shoe soles, which is composed of component A and component B. Component A includes (by weight) 10-90 parts of low-cost polycarbonate polyol, 90-10 parts of common polyester polyol, 5-30 parts of small molecule diol chain extender, 0-10 parts of cross-linking agent, 0.2-10 parts of tertiary amine or organic metal catalyst, 0.2-2.5 parts of organic silicon foam leveling agent, and 0.01-5 parts of water / physical foaming agent; component B includes (by weight) 40-80 parts of isocyanate, 60-20 parts of common polyester polyol, and 10-200ppm of side reaction inhibitor.
[0005] CN101486801B discloses a low-density polyurethane microporous elastomer sole material with added thermal foaming microspheres, which is obtained by reacting component A and component B. Component A comprises, by weight: polyester polyol A1: 60-90; polyester polyol A2: 10-40; chain extender: 5-15; crosslinker: 0.15-0.4; foaming agent: 0.5-2; foam leveling agent: 0.2-1.5; catalyst: 1-3; thermal foaming microspheres: 1-20. The polyester polyol A1 is a polyester polyol with a number average molecular weight of 1500-2500 obtained by ester exchange reaction between one or more of ethylene glycol, diethylene glycol, 1,4-butanediol and adipic acid; the polyester polyol A2 is a polyester polyol with a number average molecular weight of 2000-2500 prepared by free radical polymerization of olefin monomers in polyester polyol A1, and the grafting rate is 20-25%; the chain extender is selected from ethylene glycol, 1,2-propylene glycol, etc.; the cross-linking agent is selected from trimethylolpropane, glycerol, etc.; the foaming agent is a mixture of water and 1,1-dichloro-1-fluoroethane; the foam leveling agent is a polyether modified silicone surfactant; the catalyst is selected from triethylenediamine, dibutyltin dilaurate, etc. Component B includes: diisocyanate: 100; polyester polyol B1: 30-45; polyether polyol: 5-25; side reaction inhibitor: 10-100 ppm (relative to the weight of the polyol); wherein polyester polyol B1 is a polyester polyol with a number average molecular weight of 1500-2500 obtained by ester exchange reaction of one or more of ethylene glycol, diethylene glycol, 1,4-butanediol, and neopentyl glycol with adipic acid; polyether polyol is selected from polyoxypropylene polyol and the like; and side reaction inhibitor is selected from inorganic acid, organic acid or benzoyl chloride.
[0006] CN102040723B discloses a polyurethane elastomer composition for shoe materials, which consists of two components: Component A: In terms of weight percentage, 82%-93.5% of a polymer polyol with a number average molecular weight of 1000-2000 and a functionality of 2, 5%-15% of a chain extender, 1%-2% of an anti-aging agent, and 0.5%-1.0% of a catalyst are dehydrated at 100-110° C. and below -0.095 MPa to a water content of less than 0.05% to obtain a polymer component, wherein the polymer polyol is selected from polyester polyol or polytetramethylene ether polyol. Alcohol, catalyst is selected from one or more of dibutyltin dilaurate, organic zinc, organic bismuth, chain extender is selected from one or more of ethylene glycol, 1,4-butanediol, trimethylolpropane, anti-aging agent is selected from one or more of UV-9, UV-531, UV-328, UV-329, 1010, BHT, 1076; component B: a modified diisocyanate selected from diphenylmethane diisocyanate, carbonized diimide modified MDI and their mixture, and its isocyanate mass content is 20%-30%. Components A and B are mixed in a mass ratio of 100:40-60 to obtain a polyurethane elastomer for shoe materials with a hardness of Shore A60-80.
[0007] CN103044898B discloses a cell opener for polyurethane elastomer, which comprises polybutadiene and fumed silica, and the weight ratio is: polybutadiene: fumed silica = 1:4-7:1. The cell opener reacts with oligomer polyol, catalyst, foaming agent (water), foam leveling agent silicone oil, chain extender, and diisocyanate to prepare polyurethane elastomer.
[0008] CN104072716B discloses a polyurethane elastomer shoe material, which is prepared by uniformly mixing a composition containing 20-22 parts by weight of diisocyanate, 8-10 parts by weight of polyester polyol, 5-6 parts by weight of polymer polyol, 5-6 parts by weight of 1,4-butanediol, 1.8-2.0 parts by weight of polyethylene-vinyl acetate copolymer, 1.2-1.5 parts by weight of diethylaminoethyl methacrylate, 0.20-0.25 parts by weight of triethylenediamine, 0.40-0.50 parts by weight of water (foaming agent), and 0.25-0.30 parts by weight of a foam leveling agent, and then injecting the mixture into a preheated mold of a predetermined shape for reaction and curing.
[0009] CN106117504B discloses a polyurethane elastomer sole material, comprising a fabric core layer, on the outer surface of which a polyurethane elastic layer is cast; the fabric core layer is woven from spandex fiber and aramid fiber. Before casting, the fabric core layer is subjected to radio frequency plasma modification treatment, and the polyurethane elastic layer is cast in a mold by mixing a prepolymer component and an oligomer component to obtain a casting composition.
[0010] CN110724298A discloses a method for preparing graphene wear-resistant rubber-plastic foamed shoe materials, which comprises: 1. mixing graphene and aluminum powder in a mass ratio of 5:1, melting and mixing the obtained mixed powder at a high temperature of 660-680°C, and then spraying to obtain flaky nano-scale graphene / aluminum powder; 2. mixing polycarbonate diol, 4,4'-diphenylmethane diisocyanate, and stannous octoate, adding flaky nano-scale graphene / aluminum powder and sodium hexametaphosphate dispersant, and stirring the mixture at 80-100°C. , to obtain a polycarbonate polyurethane elastomer containing graphene / aluminum; 3. The polycarbonate polyurethane elastomer containing graphene / aluminum is mixed with EVA, NR rubber, inorganic filler, lubricant, sulfur, AC foaming agent (azodicarbonamide), and antioxidant in a mass ratio of 8:50-100:5-10:3-5:1-2:1.5-3:0.05-0.2:0.5-1 in an internal mixer, and the sheet is produced through an open mixer; 4. The sheet obtained in step 3 is cut according to demand, and is implanted in a mold for foaming. The flaky nano-scale graphene / aluminum powder obtained in step 1 is mainly aluminum element loaded on the surface of flaky graphene.
[0011] CN113754857A discloses a polyurethane elastomer for rapid prototyping low-temperature resistant shoe materials and a preparation method thereof. The elastomer is made of a polymer component A and a prepolymer component B, wherein the component A is made of polyol A, a chain extender, a catalyst, an antioxidant and an anti-ultraviolet absorber; the component B is made of diisocyanate and polyol B, and its NCO content is 18-25%.
[0012] CN115304737A discloses a polyurethane elastomer for low-temperature resistant shoe materials and its preparation process. The polyurethane elastomer comprises component A and component B; the mass ratio of component A to component B is 1:(0.8-1); component A comprises the following substances: by weight, 95-105 parts of diol A, 3-4 parts of small molecule diol, 0.5-1 part of anti-wear agent, 1-2 parts of foaming agent, and 1-2 parts of catalyst; component B comprises the following substances, by weight, 38-50 parts of diol B, 52-60 parts of isocyanate, 2-3 parts of toughening agent, and 0.5-1 part of grafting agent. By using polyether polyol as the main material, supplemented by a small amount of polyester and UV-resistant 2,2'-dihydroxy-4-methoxybenzophenone as the polyol, introducing a small amount of wear-resistant agent, toughening agent and grafting agent, the mechanical properties and wear resistance are synergistically improved while ensuring the low-temperature resistance; in this way, a polyurethane elastomer with excellent yellowing resistance, low-temperature resistance and mechanical properties is prepared.
[0013] The polyurethane foam shoe material in the prior art uses a foaming agent (such as CO2 or azodicarbonamide AC or water) that is incompatible with the main foaming material (terminated hydroxyl elastomer, polytetramethyleneimine polyol or polycarbonate polyol), and the mixing uniformity between the foaming agent and the main foaming material is slightly poor, resulting in uneven distribution and uneven size of the bubbles in the prepared polyurethane foam shoe material (such as the sole substrate), which in turn leads to inconsistent resilience or density at different parts of the shoe material, affecting the quality and service life of the shoe product. Summary of the invention
[0014] In order to solve the technical problems existing in the prior art, the inventors of the present application screened out a type of foaming agent that has good compatibility with the commonly used polymer main materials (such as polytetramethylene glycol and polycarbonate polyol) used to prepare polyurethane foam shoe materials from the foaming agents developed by the company.
[0015] The uniformity of cell distribution and cell size in polyurethane foamed shoe materials (such as sole substrates) is related to the strength, resilience (comfort) and service life of the shoe products.
[0016] According to a first aspect of the present invention, there is provided a polyurethane microcellular elastomer for shoe materials, which is formed by mixing and pouring component A and component B:
[0017] 1) Component A, which comprises (by weight):
[0018] Polytetramethylene glycol with a number average molecular weight in the range of 800-2000 (preferably 1000-1500): 30-40 parts; preferably 32-38 parts; 34-36 parts;
[0019] Polybutylene adipate diol with a number average molecular weight in the range of 500-1000 (preferably 600-800): 10-20 parts; preferably 12-18 parts; preferably 14-16 parts;
[0020] Catalyst: 0.4-2.2 parts; preferably 0.45-2.0 parts; 0.5-1.8 parts; 0.55-1.6 parts; such as 0.6, 0.7, 0.8, 1, 1.2, 1.4 or 1.5 parts;
[0021] Foam stabilizer: 0.7-2.5 parts; preferably 0.8-2.4 parts; preferably 1-2.3 parts; 1.2-2.0 parts; such as 1.4 parts, 1.6 parts or 1.8 parts;
[0022] Aqueous alcohol amine foaming agent: 3-6 parts; preferably 3.5-5.5 parts; 4-5 parts;
[0023] Butanediol chain extender: 0-3.5 parts; preferably 0.1-3.4 parts, 0.5-3.2 parts; 0.6-3.0 parts; 0.7-2.8 parts; 0.8-2.5 parts, such as 1 part, 1.2 parts, 1.5 parts, 1.8 parts or 2 parts;
[0024] Silane-modified alumina nanosheets (Al2O3): 0-1.5 parts; 0.1-1.4 parts; preferably 0.15-1.3 parts; 0.2-1.2 parts; 0.25-1.0 parts; such as 0.3, 0.35, 0.4, 0.5, 0.6, 0.7 or 0.8 parts;
[0025] 2) Component B, which comprises (by weight):
[0026] NCO-terminated polyurethane prepolymer: 45-55 parts; preferably 47-53 parts; 48-52 parts; such as 50 parts;
[0027] The NCO-terminated polyurethane prepolymer is a polyurethane prepolymer formed by the reaction of an organic polyisocyanate monomer and a polycarbonate diol having a number average molecular weight in the range of 800-2000 (preferably 1000-1800).
[0028] In the present application, polybutylene adipate diol refers to polybutylene adipate diol.
[0029] Preferably, the sum of the weights of polytetramethylene ether diol and polybutylene adipate diol is 48-52 parts by weight, preferably 50 parts by weight.
[0030] Preferably, the silane-modified alumina nanosheets (Al2O3) are formed by reacting a silane coupling agent with an alumina sheet having a sheet diameter (or particle size) of 10-300 nanometers (according to a weight ratio of 0.1-0.7:1, preferably 0.2-0.6:1, preferably 0.3-0.5:1). Preferably, the silane coupling agent is selected from one or more of N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane (KH-792,), and / or 3-aminopropyltriethoxysilane (KH-550).
[0031] The organic polyisocyanate monomer is MDI (diphenylmethane diisocyanate), PMDI (polymethylene polyphenyl polyisocyanate, such as PM200 of Wanhua Chemical), TDI (toluene diisocyanate), HDI (hexamethylene diisocyanate) and / or IPDI (isophorone diisocyanate), or a trimer of HDI or IPDI, respectively (such as HDI trimer).
[0032] The NCO-terminated polyurethane prepolymer is a polyurethane prepolymer formed by the reaction of an organic polyisocyanate monomer (such as HDI or IPDI) with a polycarbonate diol having a number average molecular weight in the range of 800-2000 (preferably 1000-1800), the latter having an NCO content of 7-15wt%, such as 8-13wt%, such as 9, 10, 12wt%.
[0033] The aqueous alcohol amine blowing agent comprises the following components or consists of the following components or consists mainly of the following components: (1) ethanol sec-butanolamine (A1); (2) ethanol di-sec-butanolamine (A2); and (3) water;
[0034] Wherein, the molar ratio of ethanol di-sec-butanolamine (A2) to ethanol sec-butanolamine (A1) is (0.2-4):1, preferably (0.25-3.5):1, preferably (0.3-3):1, preferably (0.35-2.5):1, preferably (0.4-2.0):1, preferably (0.45-1.5):1, preferably (0.47-1.2):1, preferably (0.5-1):1;
[0035] Wherein, the water content is 12-30wt%, preferably 14-28wt%, preferably 15-26wt%, preferably 16-25wt%, preferably 17-24wt%, based on the total weight of the (final) aqueous alcoholamine blowing agent;
[0036] The total content of (A1) + (A2) + water is 94-100%, preferably 95-100%, preferably 95.5-100%, preferably 96-100%, preferably 96.5-100%, preferably 97-100%, preferably 98-100%, preferably 99-100%, such as 99.5 or 99.8% or 99.9%, based on the total weight of the (final) aqueous alcoholamine blowing agent;
[0037] Wherein, a portion of the alkanolamine in the aqueous alkanolamine foaming agent is neutralized by CO2 so that the CO2 content in the (final) aqueous alkanolamine foaming agent is 1-5wt%, preferably 1.2-4.7wt%, preferably 1.5-4.5wt%, preferably 1.8-4.2wt%, preferably 2-4wt%, preferably 2.5-3.8wt%, for example 3 or 3.5wt%, based on the total weight of the (final) aqueous alkanolamine foaming agent.
[0038] Preferably, the (final) aqueous alcoholamine blowing agent has a viscosity of 200-800 centipoise, preferably 250-700 centipoise (eg 300, 400, 500, 600, 650 centipoise) at an ambient temperature of 25°C.
[0039] Microcellular elastomers may also be referred to as microporous elastomers.
[0040] Preferably, the aqueous alcohol amine blowing agent is prepared by the following preparation method:
[0041] 1) Preparation of an aqueous alcoholamine foaming agent: ethanol sec-butanolamine, ethanol di-sec-butanolamine and water are mixed to obtain an aqueous alcoholamine foaming agent; wherein the amounts of ethanol di-sec-butanolamine (A2) and ethanol sec-butanolamine (A1) are such that the molar ratio of ethanol di-sec-butanolamine (A2) to ethanol sec-butanolamine (A1) in the obtained aqueous alcoholamine foaming agent is (0.2-4):1, preferably (0.25-3.5):1, preferably (0.3-3):1, preferably (0.35-2.5 ):1, preferably (0.4-2.0):1, preferably (0.45-1.5):1, preferably (0.47-1.2):1, preferably (0.5-1):1; wherein the amount of water used is such that the water content in the (final) obtained aqueous alcoholamine foaming agent is 12-30wt%, preferably 14-28wt%, preferably 15-26wt%, preferably 16-25wt%, preferably 17-24wt%, based on the total weight of the (final) aqueous alcoholamine foaming agent;
[0042] Preferably, in the (final) obtained aqueous alcoholamine blowing agent, the total content of (A1) + (A2) + water is 94-100%, preferably 95-100%, preferably 95.5-100%, preferably 96-100%, preferably 96.5-100%, preferably 97-100%, preferably 98-100%, preferably 99-100%, such as 99.5 or 99.8% or 99.9%, based on the total weight of the (final) aqueous alcoholamine blowing agent;
[0043] 2) introducing CO2 gas into the obtained aqueous alcoholamine blowing agent to partially neutralize the alcoholamine compound in the aqueous alcoholamine blowing agent, thereby obtaining a (final) aqueous alcoholamine blowing agent containing CO2;
[0044] Among them, the amount of CO2 introduced should make the CO2 content in the (final) aqueous alcoholamine foaming agent be 1-5wt%, preferably 1.2-4.7wt%, preferably 1.5-4.5wt%, preferably 1.8-4.2wt%, preferably 2-4wt%, preferably 2.5-3.8wt%, for example 3 or 3.5wt%, based on the total weight of the (final) aqueous alcoholamine foaming agent.
[0045] In the present application, "optional" means with or without (0).
[0046] The polyurethane microcellular elastomer for shoe materials of the present invention has a fine cell structure (fine cells, that is, a large number of cells per unit volume and uniform cell sizes).
[0047] The density of the polyurethane microfoam elastomer for shoe material of the present invention is 43-50Kg / cm 3Range, preferably 45-48Kg / cm 3 Range, for example 46.5Kg / cm 3 . Under the above foam density, the compressive strength of the microbubble elastomer (in the vertical direction of the shoe material plane) is 145-170 (KPa), preferably 147-165 (KPa). The closed cell rate of the microbubble elastomer is in the range of 89-93%, preferably in the range of 90-92%. The water absorption rate of the microbubble elastomer is in the range of 0.22-0.45%, preferably in the range of 0.35-0.42%. The resilience (%) of the microbubble elastomer is in the range of 28-34%. The elongation at break of the microbubble elastomer is in the range of 338-375%, preferably in the range of 341-372%. The tear strength (right angle, KN / m) of the microbubble elastomer is in the range of 87-93, and the tear strength (trouser type, KN / m) is in the range of 36-42. The average cell size (diameter) of the microcellular elastomer is 110-150 μm, preferably 120-145 μm, more preferably 125-140 μm.
[0048] Advantages of the present invention
[0049] 1. The present invention increases the elasticity of the microfoam material while improving the strength of the obtained microfoam material by using polytetrahydrofuran polyol (C4 chain segment) and aliphatic polyester polyol with a slightly longer chain segment length, and a blowing agent (wherein ethanol sec-butanolamine is used as a chain extender and ethanol di-sec-butanolamine is used as a cross-linking agent) having a slightly longer chain segment length (C4), without simply increasing the open porosity of the foam material by using a cell opener (for example, a large amount of water as a blowing agent) to improve the elasticity of the foam material.
[0050] 2. Ethanol di-sec-butanolamine (A2) and ethanol sec-butanolamine (A1) have an asymmetric structure and are mixed with each other, so that the aqueous alcohol amine foaming agent has no crystallization tendency and has a lower viscosity at ambient temperature. The aqueous alcohol amine foaming agent has good compatibility and miscibility with the oligomer polyol raw material, so that the foaming agent is fully mixed in the oligomer polyol raw material to ensure uniform foaming, so that the polyurethane microfoam elastomer for shoe materials of the present invention has a fine pore structure (fine pores, i.e., a large number of pores per unit volume and uniform pore size).
[0051] 3. By adjusting the water content and CO2 content in the aqueous alcohol amine foaming agent, the porosity and cell diameter of the obtained polyurethane microfoam elastomer for shoe materials are controlled. Although the polyurethane microfoam elastomer of the present invention has a lower porosity, it still has sufficient elasticity, and the elasticity and cell diameter meet the comfort requirements of the sole material. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 is a SEM photograph of the microcellular foam of Example 1.
[0053] Figure 2 is a SEM photograph of the microcellular foam of Comparative Example 1.
[0054] Figure 3 is a sample of the olamine product of Preparation Example 2 1 H-NMR spectrum. DETAILED DESCRIPTION
[0055] The present invention further describes the technical scheme in detail through the following examples, but the present invention is not limited to these examples.
[0056] Unless otherwise specified, the devices used in the examples are all devices commonly used in the art and commercially available on the market.
[0057] Method for measuring the content of alcoholamines: In the embodiments, the content of various alcoholamines (e.g., ethanol sec-butanolamine, ethanol di-sec-butanolamine) in the aqueous alcoholamine foaming agent can be measured by gas chromatography, wherein the gas chromatograph is equipped with a hydrogen flame ionization detector (FID), and the mass concentration of the alcoholamine compound is about 10 mg / mL, which is a standard solution. Gas chromatography conditions: HP-5 capillary column (30m×0.32mm id×0.25μm, 5% phenyl methyl-siloxane); the column temperature was programmed, the initial temperature was 80℃, maintained for 3min, then increased to 250℃ at a rate of 25℃ / min, and maintained for 5min; the injection port temperature was 250℃; the detector temperature was 260℃; the carrier gas was high-purity nitrogen with a flow rate of 1.5mL / min; the fuel gas was hydrogen with a flow rate of 30mL / min; the auxiliary gas was air with a flow rate of 300mL / min; the tail gas was nitrogen with a flow rate of 25mL / min; the injection method was split injection, with a split ratio of 30:1; the injection volume was 1μL.
[0058] As aluminum oxide flakes with a flake diameter (or particle size) of 10-300 nanometers, Brofos-AlO3-10 (particle size 10nm), Brofos-AlO3-20 (20nm), Brofos-AlO3-30 (30nm), Brofos-AlO3-60 (60nm), Brofos-AlO3-100 (100nm), Brofos-AlO3-200 (200nm), and Brofos-AlO3-250 (250nm) produced by Bohuas Nano-Tech Ningbo Co., Ltd. can be used.
[0059] As polytetramethylene glycol, PTMG1000 (number average molecular weight 1000) manufactured by Jinan Yuyi Chemical Co., Ltd. and PolyTHF 1000 (number average molecular weight 1000) manufactured by BASF can be used.
[0060] As poly(1,4-butylene adipate) diol, HY-1022 (weight average molecular weight 1000, hydroxyl value 106-118 mgKOH / g) and HY-600 (Mw molecular weight 600, hydroxyl value 185-205 mgKOH / g) of Xuzhou Yihuiyang New Materials Co., Ltd. can be used.
[0061] As the polycarbonate polyol, polycarbonate diol MNF2226 (number average molecular weight 1950) from Shenzhen Munafei Technology Co., Ltd., SYHP1000 polycarbonate polyol from Shanghai Shuyu Chemical Co., Ltd., and bisphenol A type polycarbonate polyol from Hubei Chengfeng Chemical Co., Ltd. can be used.
[0062] Commonly used catalysts are selected from: dibutyltin dilaurate, 33LV (A-33): 33% triethylenediamine solution in dipropylene glycol, N,N-dimethylethanolamine, N,N-dimethylbenzylamine, 70% bis(dimethylaminoethyl) ether solution in dipropylene glycol, 70% potassium octoate solution in diethylene glycol, dibutyltin dilaurate, PT303, PT304, potassium acetate, PC-8 (N,N-dimethylcyclohexylamine), PC-5 (N,N,N,N,N-pentamethyldiethylenetriamine), PC-41 (tris(dimethylaminopropyl)hexahydrotriazine), triethanolamine, JXP-508, JXP-509, TMR-2 (2-hydroxy-N,N,N-trimethyl-1-propylamine formate, Air Products and Chemicals, USA), TMR-3, TMR-4, Dabco 2040 (Evonik Chemicals). Commonly used silicone oil foam stabilizers or silane surfactants: B8525 and B8408 from Evonik Degussa (China) Investment Co., Ltd., AK-158, AK-8805, AK-8812, AK-8809, AK-8818 and AK-8860 from Jiangsu Meside Chemical Co., Ltd., DC8545, DC1990, DC5188, DC6070, DC3042 and DC3201 from Gas & Chemicals, and silicone oil 8841 from Shanghai Maihao Chemical Technology Co., Ltd. Non-silane surfactants: LK-221 and LK-443 from Gas & Chemicals.
[0063] The water content of the aqueous alcoholamine blowing agent measured by the Karl Fischer method = the amount of free water in the hydrate + the amount of water produced by the decomposition of the carbonate. Therefore, the content of free water in the aqueous alcoholamine blowing agent (wt%) = (the water content of the carbonate alcoholamine salt hydrate measured by the Karl Fischer method) - (the amount of water produced by the decomposition of the carbonate). For example, the water content in the aqueous alcoholamine blowing agent described in the present application refers to the water content measured by the Karl Fischer method.
[0064] The test methods for various parameters of polyurethane rigid foam are carried out with reference to the following Chinese national standards GB:
[0065]
[0066] In the above table, the Z direction represents the vertical direction of the foam sample (i.e., the direction perpendicular to the plane of the shoe material), and the X direction and the Y direction represent two mutually perpendicular directions on the same horizontal plane of the sample.
[0067] The elongation at break of the microcellular elastomer is tested according to GB / T528-2009 (Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber). The right-angle and trouser-type tear strength of the microcellular elastomer is tested according to GB / T529-2009 (Determination of tear strength of vulcanized rubber or thermoplastic rubber).
[0068] Viscosity refers to the dynamic viscosity "centipoise (cP)" at 25°C.
[0069] Preparation of alumina nanosheets modified by silane coupling agent:
[0070] 0.25 kg of 3-aminopropyltriethoxysilane (KH-550) and 0.5 kg of nano-alumina sheets Brofos-AlO3-100 (100 nm, Bohuas Nanotechnology Ningbo Co., Ltd.) were added to the reactor, reacted at 50° C. with stirring for 15 hours, washed with ethanol and dried to obtain silane coupling agent modified alumina nanosheets.
[0071] Preparation of NCO-terminated polyurethane prepolymers:
[0072] 20 kg of organic polyisocyanate monomer HDI trimer (Wanhua Chemical, hexamethylene diisocyanate trimer) and 7 kg of vacuum-dried polycarbonate polyol (SYHP1000 of Shanghai Shuyu Chemical Co., Ltd., number average molecular weight 1000) were added to the reactor, heated to 75°C with stirring and then kept warm for 4 hours to react until the NCO content was 9%, thereby obtaining an NCO-terminated polyurethane prepolymer.
[0073] Preparation Example 1
[0074] Part I: Preparation of single alcohol amines
[0075] 1) 30.5 kg of ethanolamine (molecular weight 61, 500 mol) and 15.5 kg of deionized water were added to a high-pressure reactor, stirred and dissolved, and the reactor was sealed. Then, under continuous stirring, the temperature was controlled between 60-95° C. and the pressure was controlled not to be higher than 0.25 MPa. 36.07 kg of 1,2-butylene oxide (molecular weight 72.11, 500 mol) was added to the reactor in batches. After the addition of the materials, the temperature was controlled to react for 3.5 hours, and then the temperature was lowered to 40° C. Then, 82.01 kg of the reaction product (alcoholamine hydrate 1) was discharged from the reactor. Samples were taken from the product and the content of ethanol sec-butanolamine in the alcoholamine hydrate 1 was measured by gas chromatography to be 499.94 mol and 0.06 mol of ethanol di-sec-butanolamine. Its viscosity (25° C.) was 372 centipoise. The water content in the alcoholamine hydrate 1 was 18.89 wt%. The pH value was 12.21.
[0076] 2) 30.5 kg of ethanolamine (molecular weight 61,500 mol) and 22.55 kg of deionized water were added to the autoclave, stirred and dissolved, and the reactor was sealed. Then, under continuous stirring, the temperature was controlled between 60-95° C. and the pressure was controlled not to be higher than 0.25 MPa. 72.12 kg of 1,2-butylene oxide (1000 mol) was added to the reactor in batches. After the addition of the materials, the temperature was controlled to react for 3.5 hours, and then the temperature was lowered to 40° C. Then, 125.02 kg of the reaction product (alcoholamine hydrate 2) was discharged from the reactor. Samples were taken from the product and the content of ethanol di-sec-butanolamine in alcoholamine hydrate 2 was 499.97 mol and the content of ethanol sec-butanolamine was 0.03 mol by gas chromatography. Its viscosity (25° C.) was 464 centipoise. The water content in alcoholamine hydrate 2 was 18.0 wt%. The pH value was 11.56.
[0077] Part II: Compounding of Multiple Alkylamines
[0078] Four batches of 20 kg each were taken from the alcoholamine hydrate 1. For each batch, 20 kg of the alcoholamine hydrate 1 was added to a reactor, and then alcoholamine hydrate 2 and a small amount of water were added and mixed according to the molar ratio and water content in the following Table 1 to obtain four batches of alcoholamine compositions (AA1-AA4).
[0079] Table 1: Molar ratio of ethanol di-sec-butanolamine to ethanol sec-butanolamine
[0080] Alcoholamine hydrate No Molar ratio of ethanol di-sec-butanolamine to ethanol sec-butanolamine Water content, wt% Alcoholamine composition AA1 3:1 19.0 Alcoholamine composition AA2 1:1 19.0 Alcoholamine composition AA3 0.5:1 19.0 Alcoholamine composition AA4 25:1 19.0
[0081] Part 3: CO2 Neutralization and Salt Formation
[0082] The four batches of alcohol amine compositions AA1-AA4 obtained by the above compounding were added to the autoclave respectively, and carbon dioxide gas was introduced into the alcohol amine compositions AA1-AA4 respectively under the condition that the pressure of the CO2 gas output from the CO2 storage cylinder was controlled to be no higher than 0.2MPa, and the temperature was controlled between 40-50°C, and the temperature was controlled to react for 3 hours, and the pressure was released after the temperature was lowered to below 40°C, and then a small amount of water was added to make the water content in the carbonate alcohol amine salt composition reach 20wt%, and the mixture was slowly stirred for 30 minutes, and the product was released, thereby obtaining carbonate alcohol amine salt compositions No. 1-4. The CO2 content is shown in Table 2.
[0083] Table 2: CO2 content in carbonate amine salt compositions 1-4
[0084]
[0085] As the CO2 content increases, the viscosity gradually increases, indicating that part of the amine forms amine carbonate.
[0086] Preparation Example 2
[0087] 24.64 kg of ethanolamine (molecular weight 61, 404 mol) and 12.24 kg of deionized water were added to a high-pressure reactor, stirred to dissolve, and the reactor was sealed. Then, under continuous stirring, the temperature was controlled between 60-95° C., and the pressure in the reactor was controlled not to be higher than 0.3 MPa. 41.8 kg of propylene oxide (molecular weight 58, 720 mol, the molar ratio of propylene oxide to ethanolamine was 1.8:1) was added to the reactor in batches. After the addition of the materials, the temperature was controlled to react for 3 hours, and then the temperature was lowered to 40° C. Then, 78.64 kg of the reaction product (alcoholamine hydrate AA2a, or alcoholamine composition AA2a) was discharged from the reactor, and the viscosity (25° C.) was 288 centipoise. The product was sampled and the content of ethanol isopropanolamine in the amine hydrate AA2a was measured by gas chromatography. The content of ethanol diisopropanolamine was 80.9 mol, the content of ethanol diisopropanolamine was 323.1 mol, and the molar ratio of ethanol diisopropanolamine to ethanol isopropanolamine was 4:1. 1 H-NMR spectrum is shown in Figure 3 The water content of the alcoholamine hydrate AA2a was determined by Karl Fischer method to be 15.6 wt %.
[0088] Then, 40 kg of the above obtained alcohol amine hydrate AA2a is added to the autoclave, and carbon dioxide gas is introduced into the alcohol amine hydrate AA2a under the condition that the pressure of the CO2 gas output from the CO2 storage cylinder is not higher than 0.3 MPa, and the temperature is controlled between 40-50°C, and the temperature is controlled to react for 3 hours. After the temperature is lowered to below 40°C, the pressure is released and the product is discharged to obtain a carbonate alcohol amine salt composition AA2b (or alcohol amine composition AA2b), wherein the CO2 absorption is 1.76 kg (about 40 mol; CO2 content is 4.2 wt%). The dynamic viscosity (25°C) of the product AA2b is 792 centipoise. The pH of the product AA2b measured by a pH meter (Ray Magnetic PHS-3C type, Shanghai Yidian Science Instrument Co., Ltd.) is 10.6. Its decomposition temperature is between 45°C and 60°C.
[0089] Application Examples
[0090] Example 1
[0091] 1. Component A (white material component): 3.6 kg of polytetrahydrofuran ether diol (PTMG1000, number average molecular weight 1000, Jinan Yuyi Chemical Co., Ltd.), 1.4 kg of polybutylene adipate diol (HY-1022, weight average molecular weight 1000, Xuzhou Yihuiyang New Materials Co., Ltd.), 0.1 kg of catalyst TMR-2 (Air Chemicals, USA), 0.01 kg of catalyst Dabco2040 (Evonik Chemical), 0.15 kg of foam stabilizer DC3201 (Gas and Chemicals Company), 0.3 kg of carbonate amine salt composition 1 in Preparation Example 1, 0.01 kg of butanediol, and 0.07 kg of silane coupling agent modified alumina nanosheets were weighed respectively, and added into the reactor in sequence, and stirred slowly (180 rpm) for 2 hours at room temperature to mix them completely to obtain a uniform mixture (i.e., white material component).
[0092] 2. Component B (black material component): 5 kg of NCO-terminated polyurethane prepolymer.
[0093] 3. The above component A and component B were mixed in a volume ratio of 1:1 using a high pressure pouring foaming machine (RSC16 / 16, KraussMaffei, Germany) and poured into a mold at 60° C. for foaming, demolded after 8 minutes, and left to mature for 3 hours to obtain a polyurethane microcellular elastomer 1. Samples were taken for analysis.
[0094] The performance parameters of the foam product are listed in Table 3. The SEM photos of the foam product samples are shown in Figure 1The cells of the foam product are very fine. The average size of the cells of the foam product is 125μm. The foam product belongs to a micro-cell elastomer.
[0095] Example 2
[0096] Example 1 was repeated, except that the carbonate amine salt composition 2 of Preparation Example 1 was used in the same amount to replace the carbonate amine salt composition 1 in Preparation Example 1, to prepare a polyurethane microbubble elastomer 2.
[0097] Example 3
[0098] Example 1 was repeated, except that the carbonate amine salt composition 3 of Preparation Example 1 was used in the same amount to replace the carbonate amine salt composition 1 in Preparation Example 1, to prepare a polyurethane microbubble elastomer 3.
[0099] Example 4
[0100] Example 1 was repeated, except that the carbonate amine salt composition 4 of Preparation Example 1 was used in the same amount to replace the carbonate amine salt composition 1 in Preparation Example 1, to prepare a polyurethane microbubble elastomer 4.
[0101] Comparative Example 1 (Com.Ex.1)
[0102] Example 1 was repeated, except that the same amount of the carbonate alcohol amine salt composition AA2b of Preparation Example 2 was used instead of the carbonate alcohol amine salt composition 1 in Preparation Example 1 to obtain a polyurethane microcellular elastomer 5. The SEM photograph of the sample of the foam product is shown in Figure 2 The average size of the cells of the foam product is 127 μm, and the foam product belongs to microbubbles.
[0103] The cell size of the microbubbles of Example 1 is slightly more uniform than that of the microbubbles of Comparative Example 1. This indicates that the miscibility between the aqueous alcohol amine blowing agent containing a sec-butyl alcohol group and the polymer polyol (polytetramethylene glycol and polybutylene adipate diethanol) is better than that of the aqueous alcohol amine blowing agent containing an isopropyl alcohol group.
[0104] Table 3 - Performance parameters of microcellular elastomers
[0105]
[0106]
[0107] Note: The compressive strength is measured on the foam specimen in the Z direction (the direction perpendicular to the plane of the shoe material).
[0108] It can be seen from Table 3 above that by using the aqueous alcohol amine foaming agent containing a secondary butanol group of the present invention, the elasticity of the microfoam material can be increased while improving the strength properties of the obtained microfoam material. Although the polyurethane microfoam elastomer of the present invention has a higher closed cell rate (lower open cell rate) and a smaller cell diameter, it still has sufficient resilience to meet the comfort requirements of the sole material.
Claims
1. Polyurethane microfoam elastomer for shoe materials, which is formed by mixing and pouring component A and component B: 1) Component A, by weight, comprising: Polytetramethylene glycol with a number average molecular weight in the range of 800-2000: 30-40 parts; Polybutylene adipate diol with a number average molecular weight in the range of 500-1000: 10-20 parts; Catalyst: 0.4-2.2 parts; Foam stabilizer: 0.7-2.5 parts; Aqueous alcohol amine foaming agent: 3-6 parts; Butanediol chain extender: 0-3.5 parts; Silane-modified alumina nanosheets: 0-1.5 parts; 2) Component B, which comprises, by weight: NCO-terminated polyurethane prepolymer: 45-55 parts; The NCO-terminated polyurethane prepolymer is a polyurethane prepolymer formed by reacting an organic polyisocyanate monomer with a polycarbonate diol having a number average molecular weight in the range of 800-2000; The aqueous alcohol amine foaming agent comprises the following components: (1) ethanol sec-butanolamine (A1); (2) ethanol di-sec-butanolamine (A2); and (3) water; The molar ratio of ethanol di-sec-butanolamine (A2) to ethanol sec-butanolamine (A1) is (0.2-4):1; The water content is 12-30 wt %, based on the total weight of the aqueous alcoholamine blowing agent; The total content of (A1) + (A2) + water is 95-100%, based on the total weight of the aqueous alcoholamine blowing agent; Wherein, a part of the alcohol amine in the aqueous alcohol amine foaming agent is neutralized by CO2 so that the content of CO2 in the aqueous alcohol amine foaming agent is 1-5wt% based on the total weight of the aqueous alcohol amine foaming agent.
2. The polyurethane microfoam elastomer for shoe materials according to claim 1, wherein 1) Component A, by weight, comprising: Polytetramethylene glycol with a number average molecular weight in the range of 800-2000: 32-38 parts; Polybutylene adipate diol with a number average molecular weight in the range of 500-1000: 12-18 parts; Catalyst: 0.45-2.0 parts; Foam stabilizer: 0.8-2.4 parts; Aqueous alcohol amine foaming agent: 3.5-5.5 parts; Butanediol chain extender: 0.1-3.4 parts; Silane-modified alumina nanosheets: 0.1-1.4 parts; 2) Component B, which comprises, by weight: NCO terminated polyurethane prepolymer: 47-53 parts.
3. The polyurethane microfoam elastomer for shoe materials according to claim 2, wherein 1) Component A, by weight, comprising: Polytetramethylene glycol with a number average molecular weight in the range of 800-2000: 34-36 parts; Polybutylene adipate diol with a number average molecular weight in the range of 500-1000: 14-16 parts; Catalyst: 0.5-1.8 parts; Foam stabilizer: 1-2.3 parts; Aqueous alcohol amine foaming agent: 4-5 parts; Butanediol chain extender: 0.5-3.2 parts; Silane-modified alumina nanosheets: 0.15-1.3 parts; 2) Component B, which comprises, by weight: NCO terminated polyurethane prepolymer: 48-52 parts.
4. The polyurethane microfoam elastomer for shoe materials according to any one of claims 1 to 3, wherein The molar ratio of ethanol di-sec-butanolamine (A2) to ethanol sec-butanolamine (A1) is (0.25-3.5):1; in, The water content is 14-28 wt %, based on the total weight of the aqueous alcoholamine blowing agent; The total content of (A1) + (A2) + water is 95.5-100%, based on the total weight of the aqueous alcoholamine blowing agent; A portion of the alcohol amine in the aqueous alcohol amine blowing agent is neutralized with CO2 so that the content of CO2 in the aqueous alcohol amine blowing agent is 1.5-4.5 wt% based on the total weight of the aqueous alcohol amine blowing agent.
5. The polyurethane microfoam elastomer for shoe materials according to any one of claims 1 to 4, wherein The molar ratio of ethanol di-sec-butanolamine (A2) to ethanol sec-butanolamine (A1) is (0.3-3):1; The water content is 15-26 wt %, based on the total weight of the aqueous alcoholamine blowing agent; The total content of (A1) + (A2) + water is 96-100%, based on the total weight of the aqueous alcoholamine blowing agent; A portion of the alcohol amine in the aqueous alcohol amine blowing agent is neutralized with CO2 so that the content of CO2 in the aqueous alcohol amine blowing agent is 2-4 wt% based on the total weight of the aqueous alcohol amine blowing agent.
6. The polyurethane microcellular elastomer for shoe materials according to any one of claims 1 to 5, wherein The organic polyisocyanate monomer is MDI, PMDI, TDI, HDI and / or IPDI, or a trimer of HDI or IPDI, respectively; and / or The NCO content of the NCO-terminated polyurethane prepolymer is 7-15 wt%. The silane-modified alumina nanosheets are formed by reacting a silane coupling agent with an alumina sheet with a sheet diameter of 10-300 nanometers in a weight ratio of 0.1-0.7:
1.
7. The polyurethane microfoam elastomer for shoe materials according to claim 6, wherein The NCO content of the NCO-terminated polyurethane prepolymer is 8-13 wt %, such as 9, 10, 12 wt %. The silane-modified alumina nanosheets are formed by reacting a silane coupling agent with an alumina sheet with a sheet diameter of 10-300 nanometers in a weight ratio of (0.2-0.6):1, preferably (0.3-0.5):
1.
8. The polyurethane microfoam elastomer for shoe materials according to claim 6 or 7, wherein The silane coupling agent is one or more selected from N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane (KH-792), and 3-aminopropyltriethoxysilane (KH-550).
9. The polyurethane microcellular elastomer for shoe materials according to any one of claims 1 to 8, wherein The density of polyurethane microfoam elastomer for shoe materials is 43-50Kg / cm 3 Range, preferably 45-48Kg / cm 3 scope.
10. The polyurethane microcellular elastomer for shoe materials according to any one of claims 1 to 9, wherein The closed cell ratio of the microcellular elastomer is in the range of 89-93%, preferably in the range of 90-92%; The rebound rate (%) of the microcellular elastomer is in the range of 28-34%; The average cell size of the microcellular elastomer is 110-150 μm, preferably 120-145 μm, more preferably 125-140 μm.
Citation Information
Patent Citations
Polyester type polyurethane micropore elastomer added with low cost polycarbonate polyatomic alcohol and preparation thereof
CN101328254B
Low density polyurethane micropore elastomer added with thermal foamable microsphere and preparation thereof
CN101486801B
Polyurethane elastomer composition for shoe material
CN102040723B
Pore-forming agent for polyurethane elastomers and application of pore-forming agent
CN103044898B
Polyurethane elastomer and sole made therefrom
CN104072716B